TECHNOLOGY AND SUSTAINABILITY: COOKIES MADE FROM THE BY-PRODUCT OF THE CARIRI CASHEW REGION (REMUNOM, 2025)
Cashew production is of great economic importance to northeastern Brazil, particularly the state of Ceará, which is the largest producer of cashew nuts, a product of global commercial significance. However, a large part of cashew stalk production is wasted, generating residues that, without proper planning, end up being underutilized or directed to other purposes, such as animal feed or agricultural inputs. This raises the need for sustainable practices. The objective of this study was to obtain flour from the co-product of cashew processing and its application in cookie formulations. Five formulations were developed, varying the proportions of cashew flour: F1 (100% wheat flour), F2 (50% wheat and 50% cashew), F3 (100% oats), F4 (50% oats and 50% cashew), and F5 (100% cashew). The results obtained were standard color content for baking formulation F4, with moisture varying from 8.88% to 11.20%, showing a proportional increase with the presence of cashew, without compromising the limits established by legislation. Ash content ranged from 1.54% to 2.54%, with F3 standing out, while formulations with cashews (F2, F4, and F5) were within the 2.5% limits. The pH of the samples ranged from 4.81 to 8.35, being lower in formulations with higher cashew content, reflecting the increase in acidity, which ranged from 0.37% to 4.21%. It can be concluded that the use of cashew co-product flour is viable for the development of cookies, constituting a product with market potential, representing a viable alternative for the use of waste obtained from local industry, adding value to products.Keywords:Anacardium occidentale L.; Use; Plant waste; Sustainability